School nursing: New ways of working with children and young people during the Covid‐19 pandemic: A scoping review. (21st December 2022) - Cook, Georgia; Appleton, Jane V.; Bekaert, Sarah; Harrold, Tikki; Taylor, Julie; Sammut, Dana
Abstract: Aim: To examine how school nurse practice evolved as a result of the Covid‐19 pandemic. Design: A scoping review of international literature, conducted and reported in line with Arksey and O'Malley's (2005) framework. Data Sources: Searches were conducted in September 2021. Ten databases were searched: The British Nursing Database, CINAHL, Cochrane Library, Consumer Health Database, Health and Medicine, Nursing and Allied Health, Public Health, PsycINFO, PubMed and Web of Science. Relevant grey literature was identified through hand searching. Review Methods: A minimum of three reviewers independently screened articles and two reviewers independently undertook data extraction, with any decisions made collaboratively with the wider team. Much of the literature was not empirical work and so it was not possible to apply a traditional quality appraisal framework. Results: Searches identified 554 papers (after deduplication) which were screened against title and abstract. Following the full‐text review, 38 articles underwent data extraction and analysis. The review findings highlighted that school nurses adapted their practice to ensure they were able to continue providing their formal and informal school health offer to children, young people and their families and continued working closely with the multidisciplinary team. In addition, the expanded public health role generated by Covid‐19 for school nurses' work was considerable, multi‐layered and added to their routine workload. School nurses displayed resilience, adaptability and creativity in their response to delivering services during Covid‐19. Conclusion: School nurses took on a leading public health role during the Covid‐19 pandemic. Some developments and practices were highlighted as beneficial to continue beyond the pandemic. However, formal evaluation is needed to identify which practices may merit integration into routine practice. Continued investment in staff and infrastructure will be essential to ensuring school nurses continue to expand their practice and influence as public health experts.